Unravelling the roles of innate lymphoid cells in cerebral malaria pathogenesis. (29th January 2018) - Palomo, J.; Quesniaux, V. F. J.; Togbe, D.; Reverchon, F.; Ryffel, B.
Summary: Cerebral malaria (CM) is one complication of Plasmodium parasite infection that can lead to strong inflammatory immune responses in the central nervous system (CNS), accompanied by lung inflammation and anaemia. Here, we focus on the role of the innate immune response in experimental cerebral malaria (ECM) caused by blood‐stage murine Plasmodium berghei ANKA infection. While T cells are important for ECM pathogenesis, the role of innate lymphoid cells (ILCs) is only emerging. The role of ILCs and non‐lymphoid cells, such as neutrophils and platelets, contributing to the host immune response and leading to ECM and human cerebral malaria (HCM) is reviewed.